Narcolepsy risk loci outline role of T cell autoimmunity and infectious triggers in narcolepsy - Ollila, Hanna M; Sharon, Eilon; Lin, Ling; Sinnott-Armstrong, Nasa; Ambati, Aditya; Yogeshwar, Selina M; Hillary, Ryan P; Jolanki, Otto; Faraco, Juliette; Einen, Mali; Luo, Guo; Zhang, Jing; et al. (Nature communications, 2023)
Narcolepsy type 1 (NT1) is caused by a loss of hypocretin/orexin transmission. Risk factors include pandemic 2009 H1N1 influenza A infection and immunization with Pandemrix®. Here, we dissect disease mechanisms and interactions with environmental triggers in a multi-ethnic sample of 6,073 cases and 84,856 controls. We fine-mapped GWAS signals within HLA (DQ0602, DQB1*03:01 and DPB1*04:02) and discovered seven novel associations (CD207, NAB1, IKZF4-ERBB3, CTSC, DENND1B, SIRPG, PRF1). Significant signals at TRA and DQB1*06:02 loci were found in 245 vaccination-related cases, who also shared polygenic risk. T cell receptor associations in NT1 modulated TRAJ*24, TRAJ*28 and TRBV*4-2 chain-usage. Partitioned heritability and immune cell enrichment analyses found genetic signals to be driven by dendritic and helper T cells. Lastly comorbidity analysis using data from FinnGen, suggests shared effects between NT1 and other autoimmune diseases. NT1 genetic variants shape autoimmunity and response to environmental triggers, including influenza A infection and immunization with Pandemrix®.
Keywords: vakcíny proti chřipce; Autoimmune Diseases; Autoimmunity; Influenza A Virus, H1N1 Subtype; autoimunita; Narcolepsy; Influenza Vaccines; chřipka lidská; autoimunitní nemoci; Humans; lidé; narkolepsie; virus chřipky A, podtyp H1N1; Influenza, Human